The water will come : rising seas, sinking cities, and the remaking of the civilized world - Goodell, Jeff (Little, Brown and Company, 2017)
"What if Atlantis wasn't a myth, but an early precursor to a new age of great flooding? Across the globe, scientists and civilians alike are noticing rapidly rising sea levels, and higher and higher tides pushing more water directly into the places we live, from our most vibrant, historic cities to our last remaining traditional coastal villages. With each crack in the great ice sheets of the Arctic and Antarctica, and each tick upwards of Earth's thermometer, we are moving closer to the brink of broad disaster. By century's end, hundreds of millions of people will be retreating from the world's shores as our coasts become inundated and our landscapes transformed. From island nations to the world's major cities, coastal regions will disappear. Engineering projects to hold back the water are bold and may buy some time. Yet despite international efforts and tireless research, there is no permanent solution-no barriers to erect or walls to build-that will protect us in the end from the drowning of the world as we know it. The Water Will Come is the definitive account of the coming water, why and how this will happen, and what it will all mean. As he travels across twelve countries and reports from the front lines, acclaimed journalist Jeff Goodell employs fact, science, and first-person, on-the-ground journalism to show vivid scenes from what already is becoming a water world"--Amazon.com.